Die Stadt als Theater - eine kulturanthropologische sicht auf Dubrovnik von der fruhen Neuzeit bis 1992 - Čale-Feldman, Lada (1997)
Die Stadt als Theater - eine kulturanthropologische sicht auf Dubrovnik von der fruhen Neuzeit bis 1992
Projekt MZOS
GER